Therapeutic Effect and Safety of Granulocyte Colony-Stimulating Factor Therapy for Acute-On-Chronic Liver Failure: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Hou, Xiaoxue; Li, Yuwen; Yuan, Hui; Cai, Jinyuan; Liu, Rui; Li, Jun; Zhu, Chuanlong (Frontiers in Medicine, 2021)
Background and Aims: Granulocyte colony-stimulating factor (G-CSF) has been proposed as a therapeutic option for patients with acute-on-chronic liver failure (ACLF). However, its clinical efficacy remains debatable. This study aimed to synthesize available evidence on the efficacy of G-CSF in ALCF. Methods: The Cochrane Library, CNKI, MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL), and ClinicalTrials.gov were searched from inception until September 2021. After qualitative evaluation of the included literature, the included studies were analyzed. Results: Seven studies were included in this meta-analysis. Overall, G-CSF therapy was not associated with a reduced risk of death (30-day survival, OR = 1.55, 95% CI: 1.00, 2.38, P = 0.05; 60-day survival, OR = 1.50, 95% CI: 0.95, 2.36, P = 0.08; 90-day survival, OR = 1.61, 95% CI: 0.99, 2.62, P = 0.05) or complication including occurrence of infections infection (OR = 0.66, 95% CI: 0.41, 1.05, P = 0.08), bleeding (OR = 1.50, 95% CI: 0.58, 3.89, P = 0.41), and hepatorenal syndrome (OR = 0.56, 95% CI: 0.25, 1.24, P = 0.15). Moreover, it had no obvious beneficial effects on the model of end-stage liver disease score (30-day SMD = −3.31, 95%CI: −7.42, 0.81, P = 0.12; 60-day SMD = −1.23, 95% CI: −5.21, 2.75, P = 0.54; 90-day SMD = −2.29, 95%CI: −4.94, 0.37, P = 0.09). Sensitivity analyses showed that patients in Asia had improved survival (30-day OR = 2.76, 95%CI: 1.43, 5.35, P = 0.003; 60-day OR = 2.83, 95% CI: 1.39, 5.73, P = 0.004; 90-day OR = 2.92, 95% CI: 1.34, 6.36, P = 0.007). Conclusions: Our findings suggest that, currently, G-CSF cannot be recommended for the treatment of ACLF.